2024
DOI: 10.3390/plants13071009
|View full text |Cite
|
Sign up to set email alerts
|

High-Value Compounds in Papaya By-Products (Carica papaya L. var. Formosa and Aliança): Potential Sustainable Use and Exploitation

Ana F. Vinha,
Anabela S. G. Costa,
Liliana Espírito Santo
et al.

Abstract: Background: Food waste is a global and growing problem that is gaining traction due to its environmental, ethical, social, and economic repercussions. Between 2022 and 2027, the worldwide papaya market is expected to have a huge increase, meaning a growth in organic waste, including peels and seeds. Thus, this study evaluated the potential use of peels and seeds of two mature papaya fruits as a source of bioactive compounds, converting these by-products into value-added products. Proximate analysis (AOAC metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…While papaya (mainly its fruit) can be eaten fresh, it is acknowledged to be generally used in food manufacturing industries to make processed foods (mainly the fruit pulp), while other parts such as the peel and seeds are discarded [13]. Some earlier reports have reported that around 32% of non-edible pulp, 8.47% of peel, and 6.51% of seeds are produced as waste during industrial food processing which are mostly discarded as food waste materials [13][14][15][16]. The accumulation of huge amounts of papaya peels (food waste) after its pulp is utilized remains an environmental issue, as the solid wastes transmit life-threatening diseases and there are no sustainable management systems for this huge and year-round production of bioresource waste materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While papaya (mainly its fruit) can be eaten fresh, it is acknowledged to be generally used in food manufacturing industries to make processed foods (mainly the fruit pulp), while other parts such as the peel and seeds are discarded [13]. Some earlier reports have reported that around 32% of non-edible pulp, 8.47% of peel, and 6.51% of seeds are produced as waste during industrial food processing which are mostly discarded as food waste materials [13][14][15][16]. The accumulation of huge amounts of papaya peels (food waste) after its pulp is utilized remains an environmental issue, as the solid wastes transmit life-threatening diseases and there are no sustainable management systems for this huge and year-round production of bioresource waste materials.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of huge amounts of papaya peels (food waste) after its pulp is utilized remains an environmental issue, as the solid wastes transmit life-threatening diseases and there are no sustainable management systems for this huge and year-round production of bioresource waste materials. Thus, the use of papaya food waste materials such as peels in a sustainable manner can add to decreasing food insecurity and enhance food sustainability, specifically in the underdeveloped countries of the world [16]. There is a report of ripened papaya peels used as biofertilizers [17].…”
Section: Introductionmentioning
confidence: 99%